An Investigation into the Role of Supply-Side Factors in the Implementation of Management Accounting Innovations within the Industrial Companies in UAE: A Questionnaire Survey - Nassar, Mahmoud (Opción, 1970)
This paper focuses on the diffusion of management accounting innovations (MAIs) in UAE with the objectives (i) to determine the role of supply-side factors on decisions implementing MAIs within the UAE industrial sector, and (ii) ascertain the level of satisfaction among the allied UAE companies, concerning the role of these factors in driving the diffusion process. By applying a multi-method approach, (a combination of questionnaire survey and semi-structured interviews), conducted in two sequential stages, the study used the mixed methods of data collection and analysis. About rating the importance of various factors driving the diffusion of MAIs, 33 companies, who implemented MAIs, reported that consultant companies and accounting education were the most important factors influencing them to implement MAIs.